Lubricant ester synthesis from rubber seeds waste using cockle shells as solid catalyst - Ng, Wei Keong (2013)
This paper presents the lubricant ester synthesis from rubber seeds waste using cockle shells as solid catalyst. Rubber seeds were chosen as raw materials in synthesizing lubricant because it is a type non-edible resource and this can avoid the problem of shortcoming on human foods. Rubber seed and cockle shell was abundance in Malaysia and causing waste problem. The kernel of rubber seed was milled into average size of 1mm in diameter. N-hexane is used as solvent in microwave assisted extraction of rubber seed oil. The catalyst that used in this research is cockle shells due to the high content on CaCO3 which can be converted into CaO. The cockle shells was cleaned and crushed into smaller particles before undergoes calcination process. Then, the activated and inactivated catalysts was analysed using X-ray Fluorescence (XRF), and Fourier transforms infrared (FTIR) spectroscopy analysis. N-hexane was used as solvent in microwave assisted extraction of rubber seed oil. Two steps transesterification process was applied in order to reduce the fatty acid content in the rubber seed oil. The rubber seed oil extracted from rubber seeds underwent two steps esterification process to produce rubber seed methyl ester (RSME). The biolubricant produced through the transesterification process of rubber seed methyl ester (RSME) and trimethylolpropane (TMP) with the presence of CaO catalyst under difference parameter of temperature, reaction time and catalyst loading. Then, the viscosity of biolubricant was analysed using viscometer.The composition of CaO in calcinated cockle shells was 97.06%. Various temperature, reaction time and catalyst loading were applied to seek the optimized result. The results shows RSME has successfully being converted into 37.8% of triester at the temperature of 110 0C, 3wt% of CaO catalyst and 3 hours of reaction time. While for viscosity of the lubricant, the kinematics viscosity of lubricant fulfill the ISO VG 46. The viscosity of lubricant was found to be higher than other plant based lubricant such as palm oil